Régimen de visitas y su incumplimiento por parte de los padres en el cantón Quevedo en el año 2021. - Morán Iza, Mabelyn Jakeline (2023)
Before beginning with the summary of the research project, allow me to transcribe a sentence "Adequate protection of minors guarantees the formation of a healthy, free and autonomous adult" fragment of the Charter of the United Nations, how accurate are these words with the subject of investigation that is the Regime of Visits and its non-compliance. It is because, by living in a state of rights and justice contemplated in our Constitution, it makes us aware that the state has to guarantee the protection of the rights of vulnerable groups, specifically referring to children under the principle of interest higher than lower The right to take advantage of the regime of views by any of the parents is protected by the Organic Code of Childhood and Adolescence, this legal institution is applied when the ties of coexistence between the parents of the minor are broken, this due to various situations these, economic, social, cultural among others. Because it is so important to you that this legal figure exists, it is simple, so that there is an affective bond between the parents and the minor and thus protect the affective-emotional sphere of the minor. However, there is a breach of said legal institution for which I will mention two types of breaches. The first on the part of the father, this occurs because they evade all kinds of responsibility with the minor, that is, to provide food, to conduct views and even lose parental authority with the minor. And the second has to do with the mother, by preventing the father from meeting with the minor, this is because he continues to have problems with the minor's father, this obstacle is the most common in our society for which our administration of justice has resolved that by issuing a resolution order in which the visiting regime is established by any of the parties, it must be complied with and failure to abide by said decree is configuring an untack to the authority, then by hindering the provisions of an authority would be incurring in a Breach of xv Legitimate Decisions of the competent Authority this in accordance with what is prescribed in our criminal legislation.